Pembinaan Pengembangan Produk Makanan Menggunakan Bahan Kearifan Lokal - Sumantika, Arsyad; Sirait, Ganda (Lembaga Riset Cendekia, Yayasan Berkah Putera Indonesia, 2023)
One of the obstacles in home businesses is not only related to product quality which is not uniform, but also in the aspect of product development. Household businesses in the Tembesi area are one area whose residents have many businesses, especially in the food sector, but are constrained in terms of quality and development. The aim of this community service is to help businesses in the Tembesi environment to carry out innovation and business development in accordance with standardization in order to create uniformity and product quality. The method used by the lecturer service team is to provide guidance and counseling to business actors in the Tembesi area. The extension material is divided into 3 categories, namely idea alignment, product innovation, and profit and loss calculations. Based on the results of the coaching, there are points that need to be considered, namely: (1) Partners feel that they are quite helped in terms of coaching, (2) Partners have a desire to improve product quality, and (3) Partners have better financial management. However, there are obstacles that must be considered, such as: (1) Not all partners agree because they still adhere to conventional principles, (2) Partners do not want to take risks because their business is already quite profitable for them. Based on this, the lecturer service team needs to further develop and carry out counseling in stages so that the program proposed by the service team can run optimally.